The Frontline CEO - Strafel, Eric (Ascent Audio, 2021)
Today, the pace of change is so great that no company can afford to wait to respond to new developments. You need nimble and creative problem solving, and the most intelligent and efficient decision-making doesn't come from the top-it comes from your employees on the frontlines who interact with customers and have the ability to see and respond to the shifting landscape before anyone else. The leaders whose organizations are best able to innovate solutions, win customers, and boost profits during this era of rapid change will be the ones who realize that everyone-from the CEO down to the frontline employee-is a leader, capitalize on that knowledge, and use it to grow. In this book, Eric Strafel draws on twenty years of experience as a top executive at Fortune 500 companies to show you how to decentralize and democratize decision-making through every level of the workforce, while ensuring that the company stays aligned, that each employee understands the company's underlying purpose, and that everyone works toward the same goal. Learn how to: leverage frontline leadership to improve corporate agility; partner with customers and with frontline employees to maximize internal innovation; create a highly engaged, empowered, and energized workforce in every department; and equip the company to break through barriers, overcome plateaus, and scale.